Prominent ‘Y’ descent is an ominous sign of a poorer prognosis in heart failure with preserved ejection fraction - Daisuke Harada (ESC Heart Failure, 2019)
Abstract Aims The heterogeneity of heart failure with preserved ejection fraction (HFpEF) represents different pathophysiological paths by which individual patients develop heart failure. The deterioration mechanisms are considered to be mainly left ventricular diastolic dysfunction, right ventricular (RV) systolic function, and RV afterload. It is unclear whether RV distensibility affects the deterioration of HFpEF. Our study aimed to clarify whether impaired RV distensibility is associated with the deterioration of HFpEF. Methods and results We retrospectively enrolled 322 patients with HFpEF and examined their echocardiography results, electrocardiograms, phonocardiograms, and jugular venous pulse waves. Using signal‐processing techniques, the prominent ‘Y’ descent of the jugular venous waveform was detected as an established haemodynamic sign of a less‐distensible right ventricle. We defined cardiovascular events of HFpEF as follows: sudden death, death from heart failure, or hospitalization for HFpEF. During a mean follow‐up period of 33 ± 20 months, 73 patients had cardiovascular events of HFpEF. The prevalence of a less‐distensible right ventricle and the variables of RV systolic pressure were independent risk factors for cardiovascular events (hazard ratio, 2.046, P = 0.005, and hazard ratio, 1.032 per 1 mmHg, P = 0.002, respectively). The event‐free rate of HFpEF was the lowest for HFpEF with a less‐distensible right ventricle and elevated RV systolic pressure (≥35 mmHg) (P for trend <0.001). Conclusions A less‐distensible right ventricle and elevated RV systolic pressure were found to be closely associated with the deterioration of HFpEF. Assessment of a less‐distensible right ventricle may help to stratify patients and improve therapeutic strategies for HFpEF.